2020
DOI: 10.1111/inr.12581
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nurses’ turnover intention at one and five years’ time

Abstract: AimThis study examined the role of job dimensions, job satisfaction, psychological stress and job burnout in predicting turnover intention at one and five years’ time among professional nurses in the Philippines.MethodsA cross‐sectional design was utilized in the study using a convenience sample of 549 registered nurses from six hospitals in the Central Philippines during the period of October 2018 to January 2019. Five self‐report scales were used in this study.ResultsOverall, 46.1% (n = 253) and 78.9% (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 32 publications
9
129
3
Order By: Relevance
“…The low number of nurses serving for more than 10 years reflects migration to other countries or shifts to other jobs (skills wastage). This is congruent to the findings of Labrague et al 44 where nurses in the Philippines are found to have high turnover intention within their first 5 years of service. Available data showed that the Philippines exported as much as 90% of its nurses to other countries abroad, 45 comprised mostly of nurses who had fewer than 10 years of work experience and had clinical experience in large hospital facility.…”
Section: Discussionsupporting
confidence: 91%
“…The low number of nurses serving for more than 10 years reflects migration to other countries or shifts to other jobs (skills wastage). This is congruent to the findings of Labrague et al 44 where nurses in the Philippines are found to have high turnover intention within their first 5 years of service. Available data showed that the Philippines exported as much as 90% of its nurses to other countries abroad, 45 comprised mostly of nurses who had fewer than 10 years of work experience and had clinical experience in large hospital facility.…”
Section: Discussionsupporting
confidence: 91%
“…As of 2018, there are approximately 3,000 nurses working all hospitals within the region, with most nurses employed in government hospitals. As a consequence of increased migration of experienced nurses to other countries, such as the UK, the United States and countries in the Middle East, the current nurse workforce in the region is composed mainly of young nurses with an average age of 27 to 35 years (Bautista et al ., 2020; Labrague et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…From 2012 to 2017, about 92,000 licensed Filipino nurses migrated to other countries to work as nurses there (Del Mundo 2018), a trend believed to be caused by a variety of factors in the Philippines including unfavourable work environment, organisational politics, unrealistic workload, lack of career enhancement and inadequate enforcement of nursing law (Bautista et al, 2019;Labrague, Gloe, McEnroe, Konstantinos, & Colet, 2018). The nursing workforce situation is expected to deteriorate considering the increasing number of nurses at all levels reporting intentions to leave their position (Labrague et al, 2020). If this situation is not addressed, such may result in an extensive shortage of both experienced nurses and those holding managerial positions.…”
Section: Introductionmentioning
confidence: 99%